Synthesis of anisotropic polymer/inorganic particles via asymmetric swelling-dissolving process - Ji, Xiang (Langmuir : the ACS journal of surfaces and colloids, 2013)
In this work, an asymmetric swelling-dissolving process of original submicrometer-sized decentered sulfonated polystyrene/silica (SPS/silica) particles in a ternary mixed solvent (water/ethanol/heptane) was first reported. Actinia-like and porous snowman-like SPS/silica composite particles are fabricated through tuning the composition of the ternary mixed solvent. Actinia-like particles, with a silica core embedded in a "blooming" SPS matrix, are obtained when the composition of the mixed solvent is 5 g/5 g/0.1 g (water/ethanol/heptane). If the amount of heptane in the mixed solvent is doubled, then porous snowman-like particles are produced. The TEM and SEM images show that silica particles are exposed in these two anisotropic SPS/silica composite particles compared with the original decentered SPS/silica particles. Considering the particles morphology and the swelling and dissolving performance of SPS in different solvents, the formation of the new-shaped anisotropic SPS/silica composite particles should be attributed to an asymmetric swelling-dissolving process; that is, the swelling-dissolving rate of SPS coating around the protruding silica part is faster than the other part of the composite particles. The anisotropic swelling-dissolving property of polymer/inorganic composite particles inspires a facile way to the fabrication of new composite particles